The nature of historical knowledge in large-scale assessments – a study of the relationship between item formats and offerings of epistemic cognition in the Swedish national test in history - Rosenlund, David (Frontiers in Education, 2023)
Issues of validity and reliability have an impact on the construction of tests. Since the 2010s, there has been increasing emphasis in Swedish education on enhancing reliability in the large-scale test system to combat grade inflation. This study aims to examine how this increased focus on reliability has affected reliability and validity in the national test in history. Accordingly, it addresses the following research question: what kinds of epistemic knowledge does the test communicate to students? The concept of epistemic cognition builds on Kuhn et al.'s discussion on epistemic understanding, regarding the balance between the objective and subjective dimensions of knowledge.Furthermore, the concept of companion meanings is used to establish a connection between the students' epistemic cognition and the properties of the items in the test. The findings show that the selected-response tasks predominantly address the objective dimension of historical knowledge, while the constructed-response tasks contain elements of both the subjective and objective dimensions of historical knowledge. The findings regarding the offerings of epistemic cognition are discussed in relation to validity, reliability, and item formats.